PROFESSIONAL COMPETENCE DEVELOPMENT: A PHENOMENOLOGICAL STUDY OF EFL TEACHERS AT SMA NEGERI 1 - ARQAM MADJID (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
Teacher’s professional competence development becomes very important in the general area of study of education, it is probably because the professional competence development of the teacher plays an important role in their performance in teaching and the interaction with the students and other members of the school community. So, the problem statement of this research are: (i) What are the EFL teacher’s at SMA Negeri 1 Parepare Perspectives on the meaning of professional competence development. The research applying a qualitative descriptive method in the form of a phenomenological study approach. The findings indicate that (i) EFL teacher’s perspectives on the meaning of professional competence development in SMA Negeri 1 Parepare are: English teacher’s professional competence development is very necessary and very helpful it feels like a re-fresh and recharge program, English teacher’s professional competence development is very influential in increasing them self-confidence at teaching and influential to the teaching quality for both professional and pedagogical competence, Professional competence development very much helped to improve their professional and pedagogical competence, EFL teacher’s professional competence development has very good and a lot of positive effects for their profession as a teacher, EFL teacher’s professional competence development is really feel indeed greatly help improve their quality in teaching.